2019
DOI: 10.1111/cas.13931
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CD induces cell growth and invasion by activating AKT/GSK‐3β/β‐catenin signaling in colorectal cancer

Abstract: The catalytic subunit p110δ of phosphoinositide 3‐kinase (PI3K) encoded by PIK3CD has been implicated in some human solid tumors. However, its roles in colorectal cancer (CRC) remain largely unknown. Here we found that PIK3CD was overexpressed in colon cancer tissues and CRC cell lines and was an independent predictor for overall survival (OS) of patients with colon cancer. The ectopic overexpression of PIK3CD significantly promoted CRC cell growth, migration and invasion in vitro and tumor growth in vivo. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
(69 reference statements)
1
39
0
1
Order By: Relevance
“…Additionally, related researches showed the over-expression of ITGAV was closely related to the development of colorectal cancer and spreading of colorectal cancer cells via perineural invasion 33 . And the high expression of PIK3CD was also proved that affected the distant metastasis and poor prognosis of colon cancer 34 . These studies indicated that the IRGs in IRGPI played an important role in the occurrence and development of cancers, suggesting that our prognostic model would have good prospect and prognostic value in metastatic melanoma.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, related researches showed the over-expression of ITGAV was closely related to the development of colorectal cancer and spreading of colorectal cancer cells via perineural invasion 33 . And the high expression of PIK3CD was also proved that affected the distant metastasis and poor prognosis of colon cancer 34 . These studies indicated that the IRGs in IRGPI played an important role in the occurrence and development of cancers, suggesting that our prognostic model would have good prospect and prognostic value in metastatic melanoma.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, depletion of PIK3CD also strengthened the positive effect of si-HOTAIRM1 on KGN cells containing increasing cell growth and inhibiting cell apoptosis. Accumulated evidence has shown that PIK3CD was primarily expressed in leukocytes and involved in the development of several hematological malignancies and solid tumors, such as glioma, neuroblastoma, glioblastoma and breast cancer [ 6 ]. However, this is the first time we have reported the function of PIK3CD on KGN cells growth and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CD, whose ectopic expression could affect the biological phenotypes of multiple cancers, was reported to regulate the PI3K signaling pathway [39]. Also, further analysis suggested it could be employed as an independent predictor for the prognosis of cancer patients [40]. Cystic fibrosis transmembrane conductance regulator (CFTR), a gene mainly expressed in epithelial cells, was found to play pivotal roles in both physiological processes and pathological stages [41].…”
Section: Discussionmentioning
confidence: 99%